IMPROVING THE QUALITY OF TEACHING THE RUSSIAN LANGUAGE IN THE (Conferencea, 2024)
Teaching the Russian language at the institute is the acquisition of knowledge of the Russian language in order to develop the ability to express a complete thought at the level of a phrase or sentence. The purpose of the article is to become familiar with and systematize the methods of modern information technologies suitable for improving the quality of teaching the Russian language at the institute.